CLASSIFICATION OF FAILURES AND DAMAGES OF STEEL SILOS - Бібік, М. В.; Бібік, В. М.; Ульченко, Р. М.; Бібік, І. О. (Academic journal Industrial Machine Building Civil Engineering, 2017)
Causes of silo damages and collapse were analyze; foundations of their correctly maintenance were examined. Keywords: steel silo, damages, collapse.